Sudden Death in Epilepsy: Basic and Translational Research - Christopher M. DeGiorgio (Frontiers Research Topics, 2018)
Sudden Death in Epilepsy (SUDEP) is a major cause of death in people with epilepsy, accounting for up to 17% of all deaths. Research interest is exploding, focusing on epidemiology, basic mechanisms, identification of risk factors, and biomarkers. New wearable technologies are approved or in development. These incorporate accelerometers and advanced heart rate detection, which are linked to smart phones. The advent of FDA approved detection devices now allows immediate intervention by family and loved ones. The next frontier for SUDEP remains effective prevention strategies, which will likely include new devices and pharmacologic interventions. This volume is organized into three sections: Basic and Physiologic Mechanisms; Clinical Risk Factors and Inventories; and Very Early Research into Pharmacologic Interventions. It is our hope that this eBook will inform clinicians of key advances in the field, and to foster and stimulate basic and translational research with one purpose: To prevent SUDEP in those at risk.